2022
DOI: 10.3389/pore.2022.1610633
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of PDGFRβ on Mononuclear Stromal/Tumor Cells in Giant Cell Tumor of Bone After Denosumab Treatment. An Immunohistochemical Study of Five Cases

Abstract: Due to the relatively high recurrence rate and the destructive nature of the tumor, the treatment of giant cell tumor is still a challenge. Denosumab appeared to be a promising candidate as a therapeutic drug. However, several studies have reported that tumors can recur during/after treatment with denosumab. Based on activated receptor tyrosine kinase signaling pattern of the stromal/tumor cells, a combination treatment with denosumab and sunitinib has recently been proposed to inhibit recurrences. This prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, our workgroup ( 1 ) published results about the activation of the tyrosine kinase receptor (PDGFRß) on mononuclear tumour cells in GCTB during denosumab treatment. According to the retrospective immunohistochemical investigation of our five patients with local recurrent GCTB we found that during denosumab treatment the giant cells were completely absent with severe or mild fibrosis, but H3F3A-positive tumour cells could be observed continuously in all cases.…”
Section: The Efficacy Of Denosumab Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our workgroup ( 1 ) published results about the activation of the tyrosine kinase receptor (PDGFRß) on mononuclear tumour cells in GCTB during denosumab treatment. According to the retrospective immunohistochemical investigation of our five patients with local recurrent GCTB we found that during denosumab treatment the giant cells were completely absent with severe or mild fibrosis, but H3F3A-positive tumour cells could be observed continuously in all cases.…”
Section: The Efficacy Of Denosumab Treatmentmentioning
confidence: 99%
“…As a consequence, osteoclasts disappear from the tumour tissue, and they are mostly replaced by loose connective tissue and newly formed bone. H3F3A-positive stromal cells can, however, be detected in the remaining tumour tissue underlining the ineffectiveness of denosumab on the tumourous stromal cells ( 1 ).…”
Section: Introductionmentioning
confidence: 99%